Separation & Identification of Organic Compounds in Lubricating Oil Additives Using TLC & GC-MS - Khalaf, Hussein I; Hassan, Mohammed J Mohammed; Hassan, Omer A (Al-Nahrain Journal of Science, 2012)
Thin layer chromatography (TLC) and Gas Chromatography-Mass Spectrometry (GC-MS) techniques are proposed for qualitative analysis of lubricating oil additives (Hitec 2915). The additives were dissolved in heptanes, extracted with mixed solvents heptane: acetonitrile (3:2) and spotted on TLC paper. The best combination solvents as developer for TLC analysis were carbon tetrachloride: heptanes (9:1) mixture. Each separated streak was scraped, redissolved in acetonitrile and evaporated to 0.5 ml volume then analyzed by GC-MS for identification. Fourteen compounds[2-Ethyl-1-hexanol; 2-(t-butyl)-phenol; 2,4-bis-(t-butyl)-1-methoxy benzene; 2,6-bis-(t-Butyl)-2,5-cyclohexadiene-1,4-dione; 2,4-bis-(t-Butyl)-phenol; 3,5 - bis- (t-Butyl)-phenol; Decanoic acid methyl ester; Tridecanol; 1,1-Diphenyl hydrazine; 1,2-Benzene dicarboxylic acid dibutyle ester; S-Triazol 1, 5-A-pyridine 8-amino 2-phenyl; Phenol-2, 6-bis-(t-butyl); Phenol-2,5-bis-(t-butyl); Phenol - 2,4,6-Tris-(t-butyl)]were identified in this study. The mass spectral data obtained for each separated compound were compared with the standard spectral data (library search similarity) of each compound.Keywords: Separation, Lubricating Oil Additives, GC-Mass, TLC.